Against deconstruction - Ellis, John M. (John Martin), 1936- (Princeton University Press, 1989)
"The focus of any genuinely new piece of criticism or interpretation must be on the creative act of finding the new, but deconstruction puts the matter the other way around: its emphasis is on debunking the old. But aside from the fact that this program is inherently uninteresting, it is, in fact, not at all clear that it is possible. ... [T]he naivete of the crowd is deconstruction's very starting point, and its subsequent move is as much an emotional as an intellectual leap to a position that feels different as much in the one way as the other. . . ."--The book
Keywords: Deconstruction.; Criticism.; Language and languages -- Philosophy.; Deconstructivism (Architecture); Déconstruction.; Critique.; Langage et langues -- Philosophie.; Déconstructivisme (Architecture); Deconstructivist.; deconstruction (theory); LITERARY CRITICISM -- Semiotics & Theory.; Criticism; Deconstruction; Language and languages -- Philosophy